The Acculturation of Chinese Cultural Values in Balinese Painting: : Historical and Aesthetic Perspectives - Karja, I Wayan (Humaniora: Journal of Indonesia Culture and Society, 2025)
The interaction between Chinese cultural values and Balinese traditions significantly influences Balinese painting, resulting in a unique artistic identity that merges visual forms and aesthetic ideas. This article examines how Chinese cultural values influence the evolution of traditional Balinese painting, with a focus on the processes of cultural adaptation and transformation. The aim is to identify and analyze how Chinese elements integrate into Balinese visual art while preserving local traditions. A qualitative research method is employed, combining a historical approach with a visual analysis of selected artworks. The research highlights various Chinese cultural influences, including the Yin-Yang philosophy, cosmological concepts, and visual motifs such as dragons, Barong Landung, Barong Ket, Chinese coins, Nekara Pejeng, Karang Sae, and Chinese-inspired patra decorations. It also examines coloring techniques, tools, and art materials that originate from or are inspired by Chinese practices. The findings indicate that Balinese artists creatively incorporate these elements through acculturation, blending them with local forms, colors, and symbols. Rather than being a passive adoption, this process results in a dynamic transformation that enriches the aesthetic and symbolic language of Balinese painting. The originality of the research lies in its systematic analysis of Chinese contributions to the visual and technical aspects of Balinese art, which are often overlooked in existing literature. The research enhances the understanding of cultural hybridity in Southeast Asian art and provides a valuable framework for studying cross-cultural influences in traditional artistic practices.